Determination of adsorption kinetics of chloride sewage of the agricultural sector energy crops, on activated carbon (2018)
In the effluents of the process of oil extraction of African palm is evidenced the high presence of chloride ions, specifically are treated the dumping of the extractor Hacienda la Cabaña, finding that the concentration of these anions exceeds the maximum Permissible in resolution 0631 of 2015 with a value of 813, 05mg/L, with the aim of reducing this pollutant, the adsorption process is proposed; however, there are few studies about this process, which is why we consider the study of the phenomenon of adsorption of ions chloride on commercial activated charcoal. Through the proposed methodology based on bibliographic review; Criteria and selection parameters are set, both of the adsorbent and the conditions of the adsorption process; such as solution PH, it is worth mentioning that the proposed phenomenon is evaluated at ph values of 5, 6 and 7, finding that at ph value 5 The activated carbon has a higher adsorption capacity, the temperature condition in which the phenomenon develops is 20 º C due or the methodologic approach; in turn it is determined that the equilibrium time is fulfilled at 20 hours that the solution is in contact with the selected activated charcoal; Once these conditions are established, we proceed with the evaluation of the isotherms proposed by Langmuir, Freundlich and Temkin, in the same way it establishes the existing correlation of the adsorption process with the pseudo first order models, pseudo second Intraparticle Order and diffusion.